2020
DOI: 10.1021/acs.orglett.9b04636
|View full text |Cite
|
Sign up to set email alerts
|

Layered Chirality Relay Model in Rh(I)-Mediated Enantioselective C–Si Bond Activation: A Theoretical Study

Abstract: A three-layer chirality relay model is proposed for Rh­(I)-mediated enantioselective siletane activation. A chiral ligand in the back layer controls the position of the alkyne-coordinated metal center in the middle layer, which then provides a chiral environment for the incoming substrate at the front layer. A two-dimensional contour map analysis further clarified this model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…Unfortunately, the reaction afforded a mixture of two components, 6aa and 6aaʹʹ , in a 55:45 ratio with full conversion under the optimized ring expansion reaction conditions due to the competitive Si−C( sp 3 ) bond and Si−C( sp 2 ) bond cleavage of 5a . The formation of 6aaʹʹ is likely attributed to the competitive migratory insertion of alkyne into the Ni–C bond, followed by an alkene isomerization and sequential reductive elimination 42 , 43 . To improve the regioselectivity in Si−C bond cleavage of benzosilacyclobutene 5a , we further screened a large set of reaction parameters, such as ligands, solvents and temperatures (Supplementary Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, the reaction afforded a mixture of two components, 6aa and 6aaʹʹ , in a 55:45 ratio with full conversion under the optimized ring expansion reaction conditions due to the competitive Si−C( sp 3 ) bond and Si−C( sp 2 ) bond cleavage of 5a . The formation of 6aaʹʹ is likely attributed to the competitive migratory insertion of alkyne into the Ni–C bond, followed by an alkene isomerization and sequential reductive elimination 42 , 43 . To improve the regioselectivity in Si−C bond cleavage of benzosilacyclobutene 5a , we further screened a large set of reaction parameters, such as ligands, solvents and temperatures (Supplementary Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The chirality of the NHC ligand restricts the position of the incoming diphenylacetylene. [23] The only difference is the position of the naphthol moiety. In the geometry of transition state 11-ts, the large steric resistance of the naphthol points to the outside, but it points towards the ligand in transition state 20-ts.…”
Section: Resultsmentioning
confidence: 99%
“…The overlay model clearly revealed that the NHC ligand is in the same position in the two transition states, whose heterocyclic plane is perpendicular to the square plane of palladium. The chirality of the NHC ligand restricts the position of the incoming diphenylacetylene . The only difference is the position of the naphthol moiety.…”
Section: Resultsmentioning
confidence: 99%
“…[16] Facing this interesting yetc hallenging task, we herein report aR h-catalyzed intermolecular silylation of C sp ÀHb ond (i.e.,t erminal alkynes) by silacyclobutanes (SCBs). As af ascinating silicon reagent, SCB has been knownt or eact with p bondsi na formal cycloaddition [17] fashion (Scheme 1a). In 2016, we reportedt he first cases where SCB serves as an efficient silylation reagent for intramolecular C sp2 ÀHa nd C sp3 ÀH s bonds [18] (Scheme 1b).…”
mentioning
confidence: 99%